2021
DOI: 10.1002/anbr.202100012
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Activated Conjugated Polymers for Antibacterial Photodynamic and Photothermal Therapy

Abstract: With the growing crisis of the availability of effective antimicrobial treatments, the use of phototherapy has gained increasing interest as an alternative to traditional antibiotic therapy. Even though phototherapy is already used in the clinic, there is an emerging interest in new materials with enhanced antimicrobial activity triggered by light. Among the different light‐responsive materials, conjugated polymers are emerging candidates with successful application in the field of antimicrobial photodynamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 112 publications
0
21
0
Order By: Relevance
“…Conjugated polymers (or semiconducting polymers) are organic materials that present useful electronic and optical properties with a broad range of technological applications. Within the biomedical field, their photoluminescence emission and photoacoustic signal have been explored for bioimaging, while their light-triggered reactive oxygen species (ROS) and heat generation capabilities have been used for photodynamic (PDT) and photothermal therapies (PTTs) for cancer and bacterial infections. ,, The useful properties of conjugated polymers depend on their inherent chemical structure and degree of polymerization, as well as on their physical conformation. , Because of the latter, both the conditions of preparation and the type of amphiphilic compounds used for their dispersion in aqueous solutions have a direct impact on their performance. As a consequence, these factors can be used to optimize the characteristics of conjugated polymer nanoparticles (CPNs) for the application sought.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers (or semiconducting polymers) are organic materials that present useful electronic and optical properties with a broad range of technological applications. Within the biomedical field, their photoluminescence emission and photoacoustic signal have been explored for bioimaging, while their light-triggered reactive oxygen species (ROS) and heat generation capabilities have been used for photodynamic (PDT) and photothermal therapies (PTTs) for cancer and bacterial infections. ,, The useful properties of conjugated polymers depend on their inherent chemical structure and degree of polymerization, as well as on their physical conformation. , Because of the latter, both the conditions of preparation and the type of amphiphilic compounds used for their dispersion in aqueous solutions have a direct impact on their performance. As a consequence, these factors can be used to optimize the characteristics of conjugated polymer nanoparticles (CPNs) for the application sought.…”
Section: Introductionmentioning
confidence: 99%
“…Photothermal therapy (PTT) and photodynamic therapy (PDT) have emerged in recent years as promising antimicrobial methods due to their many advantages, including noninvasiveness, time- and space-controllability, and lack of drug resistance. PTT employs photothermal agents to convert light energy into heat, which can ablate pathogenic bacteria through cell membrane perturbation, fatty acid melting, and protein denaturation . PDT involves the generation of reactive oxide species (ROS) via photochemical reaction between a photosensitizer and molecular oxygen under laser irradiation. , Excessive amounts of ROS can cause oxidative damages to lipids, proteins, and DNA, thereby disrupting the physiological activities and further inducing the death of bacteria. , Some investigations have shown that PTT combined with PDT can improve the sensitivities of the bacteria to both heat and ROS and thus obtain synergistic antibacterial effects. However, due to the lack of selectivity for pathogenic bacteria, these phototherapeutic methods also bring about damage to beneficial bacteria, thus causing bacterial imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers (CP) have been attracting increasing interest for manufacturing organic-based photo devices, which has greatly expanded their applications for biosensing [ 23 ], bioimaging [ 24 ], antimicrobial photoinactivation [ 20 , 21 , 25 , 26 , 27 ] and theranostics [ 28 ] due to their inherent optoelectronic properties, such as charge transport and fluorescence quantum yield [ 29 , 30 ]. For instance, the generation of ROS by CPNs under light illumination can enhance the cytotoxicity against bacteria [ 31 ]. Furthermore, a structure modification of CPNs by functionalizing them with cationic groups may significantly improve the electrostatic interaction and disruption of bacterial surfaces with and without light irradiation [ 20 , 27 ].…”
Section: Introductionmentioning
confidence: 99%